Short-term effects of Typhoon Yolanda on individual employment and per capita (family) income in the Philippines - Del Camat, Perine S. (School of Economics, University of the Philippines Diliman, 2019)
The frequent strike of typhoons in the Philippines has caused severe damage to society. The focus is on Typhoon Yolanda as it is considered as one of the strongest tropical cyclones that hit the country. These have led us to ask the immediate damage effects of Typhoon Yolanda on per capita (family) income and individual employment. We have investigated the correlation of Typhoon Yolanda_s impact on individual employment using the logistic regression, and per capita (family) income using the difference_in_difference estimation. We have exploited the Annual Poverty Indicator Survey (APIS) dataset to estimate the impact of Typhoon Yolanda on individual employment and per capita (family) income on the regional-level. Due to the limited schedule and release of the APIS dataset, the information employed in the study only came from the 2013 and 2014 surveys. The survey only ran from January 1 to June 30 in the years 2013 and 2014. We have discovered that Typhoon Yolanda caused the probability of an individual to be employed to rise during the immediate time period. Meanwhile, the per capita (family) income was not affected by Typhoon Yolanda based on the difference_in_difference outcome during the immediate time period. We believe that our study can help in developing strategies to alleviate the increasing prevalence of environmental catastrophe specifically typhoons due to climate change.